Gender Differences in Cardiovascular Risk Factors, Clinical Presentation, and Outcome of Patients Admitted with a Hypertensive Crisis at the Buea Regional Hospital, Cameroon - Clovis Nkoke; Ahmadou Musa Jingi; Jean Jacques Noubiap; Denis Teuwafeu; Cyrille Nkouonlack; Ronald Gobina; Siddikatou Djibrilla; Ali Abas; Anastase Dzudie (International Journal of Hypertension)
Background. Several recent studies have shown differences in the risk profile and outcome of cardiovascular diseases between men and women, with a dearth of data from African populations. This study aimed to examine gender differences in a group of patients from Cameroon hospitalized with a hypertensive crisis. Methods. We conducted a cross-sectional study from June 2018 until June 2019. The criteria to define a hypertensive crisis (HC) were systolic and/or diastolic blood pressure should be ≥180/110 mmHg. We compared the clinical presentation and outcome of males versus females. Results. Out of the 1536 patients admitted, 95 (6.2%) had an HC. There were 49 (51.6%) men. There was no significant age difference between men and women (52.7 years vs. 49.3 years, p=0.28). Alcohol consumption (p<0.0001), previous stroke (p=0.04), and smoking (p=0.03) were significantly higher in men compared to women. Men had a higher proportion of psychomotor agitation (p=0.05). There was an equal proportion of men and women with hypertensive emergencies. Although acute left ventricular failure was most frequent in women (46.4% vs 42.9%), cerebral infarction (14.3% vs 17.9%), and acute coronary syndrome (0% vs 7.1%) were higher in men, the differences were not statistically significant (all p>0.05). Case fatality was also higher in men compared to women but the difference was not statistically significant. Conclusions. Men admitted for an HC had a significantly higher cardiovascular risk burden and higher psychomotor agitation. However, there were no significant differences in the types of hypertensive emergencies and outcomes between men and women.